The Effect of Bamboo Dancing Method on Students Speaking Ability at SMA Negeri 1 Siborongborong - Rekolina Siahaan; Tanggapan C. Tampubolon (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
The purpose of this study is to investigate whether the method of bamboo dancing effectively in improving students speaking ability. This study applied in the class by experimental research. The population of this study was the students of the XI class at SMA Negeri 1 Siborongborong. The total of number of population was 139, and 40 students from the population were taken as the sample by using simple cluster sampling, then they divided into two groups. The first group as the experimental group was taught by applying bamboo dancing method, while the second groups as the control group was taught without applying bamboo dancing method. The instrument used for collecting the data was test in form oral test based on the materials that has been taught in treatment. The test were divided into two; pre-test and post-test. The mean of control group is 220 (11) is lower than the mean of experimental group is 500 (25). The reliability of the test was 0,68. Based on the data tobserved (5,01) is higher than the ttable (2,71) on df 38 at the level of significance (0,01). The result of this study show that teaching speaking by bamboo dancing method is more significant than that without applying bamboo dancing method.